The Effects of Telecommuting Intensity on Employee Health. Issue 8 (November 2016) - Henke, Rachel Mosher; Benevent, Richele; Schulte, Patricia; Rinehart, Christine; Crighton, K. Andrew; Corcoran, Maureen
Purpose: To investigate the influence of the intensity of telecommuting on employee health. Design: Study design comprised a longitudinal analysis of employee demographic data, medical claims, health risk assessment data, and remote connectivity hours. Setting: Data from Prudential Financial served as the setting. Subjects: Active employees ages 18 to 64 years who completed the health risk assessment between 2010 and 2011 were the study subjects. Measures: Measures included telecommuting status and intensity, and eight indicators of health risk status (obesity, depression, stress, tobacco use, alcohol abuse, poor nutrition, physical inactivity, and an overall risk measure), with employee age, sex, race-ethnicity, job grade, management status, and work location as control variables. Analysis: Health risks were determined for nontelecommuters and telecommuters working remotely ≤8, 9 to 32, 33 to 72, and ≥73 hours per month. Longitudinal models for each health risk were estimated, controlling for demographic and job characteristics. Results: Telecommuting health risks varied by telecommuting intensity. Nontelecommuters were at greater risk for obesity, alcohol abuse, physical inactivity, and tobacco use, and were at greater overall risk than at least one of the telecommuting groups. Employees who telecommuted ≤8 hours per month were significantly less likely than nontelecommuters to experience depression. There was no association between telecommuting and stress or nutrition. Conclusion: Results suggest that employees may benefit from telecommuting opportunities.